Judging state-sponsored violence, imagining political change - Leebaw, Bronwyn Anne. (Cambridge ; New York : Cambridge University Press, New York, 2011)
"This book offers a new way to think about the legacies of the Nurem berg Trials and South Africa's Truth and Reconciliation Commission, whi ch transformed the theory and practice of transitional justice"--
Introduction : transitional justice and the "gray zone" -- Human rig hts legalism and the legacy of Nuremberg -- A different kind of justice : South Africa's alternative to legalism -- Political judgment and tra nsitional justice : actors and spectators --Rethinking restorative just ice -- Remembering resistance -- Conclusion : the shadows of the past.
Includes bibliographical references (p. 189-204) and index.
Keywords: International police; Transitional justice; Political violence; Crimes against humanity